Eksistensi dan Kekuatan Penyelesaian Sengketa Secara Adat pada Tingkat Gampong - Ilyas Ilyas (Universitas Syiah Kuala, 2010)
ABSTRACT: The Act Number 44, 1999 on Special Status of the Aceh Province has been a fact that Aceh has been given several special statuses in terms of education, custom and religion. Having regard with custom, it has been followed up by the enactment of Qanun (Aceh Provincial Ordinance) Number 9, 2008 concerning the development of custom practice. Article 3 section (3) states that it is possible that if there are disputes amongst people in Gampong, the police should let the dispute are solved by applying customary law. Therefore, the dispute settlement is not only can be solved through the court but also outside of the court. The Existence and Power of Customary Law in Solving Dispute in Gampong